Analisis Pengaruh Motivasi, Persepsi Dan Sikap Konsumen Dalam Menentukan Keputusan Berbelanja Pada Pasar Tradisional Di Kota Malang (Studi Kasus Mahasiswa Manajemen Universitas Islam Malang) - Alfiyan Ardiansyah; Muhammad Mansur; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract  This research was conducted to determine the effect of Consumer Motivation, Perceptions and Attitudes on Purchasing Decisions in traditional markets in Management Department Students of the Faculty of Economics and Business, Islamic University of Malang. Quantitative methods are used in this kind of study. by employing prospective sampling with a total of 96 respondents. This study used SPSS 25 to conduct the validity, reliability, normality, classic assumption, multiple linear regression, and hypothesis test of the coefficient of determination (Adjusted R2) on the data. Partially motivational variables have a positive and significant effect on purchasing decisions, perceptions have a positive and insignificant effect on purchasing decisions, and consumer attitudes have a positive and significant effect on decisions purchases in traditional markets for Management students at the Islamic University of Malang, according to the findings of this study. Keywords: Motivation, Perception, Consumer Attitude, Purchase Decision